The natural nano-bioceramic powder production from organ pipe red coral (Tubipora musica) by a simple chemical conversion method - OKTAR, FAİK NÜZHET; GÜNDÜZ, OĞUZHAN (AUSTRALIAN CERAMIC SOCIETY, 2018)
The marine species are especially suited for the production of bioceramic nano-powders with natural methods for their use in the biomedical field. However, there are only very limited studies regarding the production and synthesis of hydroxyapatite (HAp) and tricalcium phosphate (TCP) nanomaterials from the marine structures. The structure of coral is very unique due to its similarity to bone because their structure consists of calcium carbonate that is the precursor for the synthesis of HAp. In this research, nano-bioceramic powders were produced from the organ pipe red coral (Tubipora musica) by two different simple chemical conversion methods under two different synthesis methods rather than the common hydrothermal method. The main advantages of these two methods are that they are simple and more economical in comparison to other methods used. All samples were analyzed by X-ray diffraction (XRD) and scanning electron microscope (SEM), respectively. The size and shape of converted particles and structures were controlled by adjusting the calcination temperature and most importantly the agitation-mixing rate. According to XRD and SEM results, it can be concluded that the nano-scale monetite and other calcium phosphate powders were successfully obtained by these simple methods although retained calcium carbonate also observed due to the partial conversion.
Keywords: Red corals; Monetite; Natural nano-bioceramics; Hydroxyapatite; Chemical conversion methods; CALCIUM-PHOSPHATE; SHELLS; HYDROXYAPATITE; COWRIE